Laser-induced generation of pure tensile stresses - Niemz, Markolf H.; Lin, C. P.; Pitsillides, Costas (My University, 1997)
While short compressive stresses can readily be produced by laser ablation, the generation of pure tensile stresses is more difficult. We demonstrate that a 90° prism made of polyethylene can serve to produce short and pure tensile stresses. A compressive wave is generated by ablating a thin layer of strongly absorbing ink on one surface of the prism with a Q-switched frequency-doubled Nd:YAG laser. The compressive wave driven into the prism is reflected as a tensile wave by the polyethylene-air interface at its long surface. The low acoustic impedance of polyethylene makes it ideal for coupling tensile stresses into liquids. In water, tensile stresses up to −200 bars with a rise time of the order of 20 ns and a duration of 100 ns are achieved. The tensile strength of water is determined for pure tensile stresses lasting for 100 ns only. The technique has potential application in studying the initiation of cavitation in liquids and in comparing the effect of compressive and tensile stress transients on biological media
Keywords: Lasers; Polyethylene